Testicular germ cell tumors: the changing role of the pathologist - Ronchi, Andrea; Pagliuca, Francesca; Franco, Renato (Annals of Translational Medicine; Vol 7, Supplement 6 (September 20, 2019): Annals of Translational Medicine, 2019)
Testicular germ cell tumors (TGCTs) are a heterogeneous group of neoplasms derived from neoplastic transformation of germ cells in the testis, but with different epidemiological, biological and clinical settings, from early life to adulthood. In the latest years, several studies led to a deeper understanding of the genetic and biological events characterizing the development and progression of these neoplasms, at the basis of their divergent clinical behaviour.